The African struggle for independent education: a history of Wilberforce Institute, Evaton 1905 to 1950s - Kumalo, Vusumuzi 'Vusi' Rodney (My University, 2018)
From its earliest days, Wilberforce Institute had a unique place in the history of African education in the Transvaal. The school was founded by the African Methodist Episcopal Church in 1905 as an independent educational institution, marking African reaction to mainstream missionary education that had been tainted by some second-generation evangelist missionaries and colonial bureaucrats. This faction condemned liberal education as too literary for Africans, seeing it as incompatible to the needs of the colonial cultural and economic development and fearing that it might produce men and women who would refuse to accept the colonial values inculcated in the classroom. In this crucial period, African dissatisfaction and grievances about education began to feature in African controlled newspapers, particularly Imvo Zabantsundu. This marked the beginning of a complex process of Africans searching for alternative independent education while rejecting mainstream missionary education. Several African independent schools were established throughout South Africa; Wilberforce was the prominent school in the Transvaal. From very small beginnings, Wilberforce Institute strove not simply to bolster academic skills of the African youth but also to embody the principles of self-determination, self-sufficiency and a proud African identity. The school was embraced by its founders as a symbol of a new phase of struggle, a crusade rooted in the renascent idea that Africans were a conquered nation that needed to claim intellectual and cultural autonomy before achieving political independence. As the school advanced, many of the changes took place in response to altered government attitudes and new directions in education. This study presents the neglected aspects of education in the historiography of missionary education in South Africa. It demonstrates how the long history of formal schooling in South Africa, extending back to the nineteenth century, became a contested terrain. It tracks why and how Wilberforce Institute was founded, concentrating on the period between Wilberforce's founding in 1905 and the early 1950s when the Bantu Education Department took control of most aspects of the institute. It was a period of terrible financial constraint, but also of unique independence and experimentation.
Thesis submitted in fulfilment of the requirements for the degree Doctors of Philosophy in the Department of History University of the Witwatersrand, March 2018
Keywords: Education--South Africa; Church schools--South Africa; Church and education--South Africa